Financial Feasibility Analysis of Freshwater Tilapia Fish Fisheries in Supporting Food Security in Central Sulawesi Province - Dewi Nur Asih; Arman Arman; Husnul Khotimah; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2026)
The aquaculture sector plays a crucial role in supporting food security by providing high-quality, affordable animal protein for the community. This study aims to analyse the financial feasibility of freshwater tilapia fish fisheries and their contribution to supporting food security in Central Sulawesi Province. The study was conducted at the freshwater tilapia fish fisheries of CV, Graha Sidat Mandiri in Tinggede Village, Marawola District, Sigi Regency, Central Sulawesi. The financial feasibility analysis tool used Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Profitability Index (PI), and Payback Period (PP) indicators. The data used consisted of primary data obtained through interviews and observations, as well as secondary data from business documents and related literature. The results show that the tilapia fish farming business is feasible to run with an NPV >0, a Net B/C of 1,67, a Profitability Index of 1,91, and a Payback Period of 4 years and 8 months. This indicates that freshwater tilapia fisheries provide financial benefits, exhibit high investment efficiency, and play a strategic role in supporting food availability, increasing fish consumption, and strengthening food security in Central Sulawesi Province